2021
DOI: 10.3389/fmicb.2020.619474
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the White Collar Photoreceptor WcoA on the Fusarium fujikuroi Transcriptome

Abstract: The proteins of the White Collar 1 family (WC) constitute a major class of flavin photoreceptors, widely distributed in fungi, that work in cooperation with a WC 2 protein forming a regulatory complex. The WC complex was investigated in great detail in Neurospora crassa, a model fungus in photobiology studies, where it controls all its major photoresponses. The fungus Fusarium fujikuroi, a model system in the production of secondary metabolites, contains a single WC-1 gene called wcoA. The best-known light res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…For ascomycetes, A. nidulans with its velvet complex VelB/VeA and LaeA, the global regulator of secondary metabolism, was pivotal in unraveling the triple interconnection of light with the development and regulation of natural product metabolism ( 43 ). A comparative transcriptomic study confirmed the role of light in the regulation of carotene and other natural product genes by comparing wild-type Fusarium fujikuroi to a wcoA mutant that lost the functional white collar 1 protein ( 44 ).…”
Section: Discussionmentioning
confidence: 89%
“…For ascomycetes, A. nidulans with its velvet complex VelB/VeA and LaeA, the global regulator of secondary metabolism, was pivotal in unraveling the triple interconnection of light with the development and regulation of natural product metabolism ( 43 ). A comparative transcriptomic study confirmed the role of light in the regulation of carotene and other natural product genes by comparing wild-type Fusarium fujikuroi to a wcoA mutant that lost the functional white collar 1 protein ( 44 ).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, in the transcriptome we found a strong reduction in the number of transcripts responsive to blue light in the Δ blr -1 mutant, which shows that it is the main photoreceptor within the blue light perception system in T. atroviride . It was recently described in Fusarium fujikuroi that a drastic decrease occurs in the mRNA levels of carotenoid genes, as well as morphological and metabolic changes in a mutant of the wco A gene, encoding a White-Collar 1 orthologue ( Pardo-Medina et al, 2021 ). This result is quite interesting since this analysis was carried out early (15, 60, and 240 min) upon exposure to constant light of the WT and the wcoA strains and their results coincide with ours at 30 min, even though these two species of fungi are phylogenetically distant.…”
Section: Discussionmentioning
confidence: 99%
“…Another general regulator of special interest is LaeA [70], which is associated with light regulation and development control with Velvet proteins forming a complex [71,72]. It has recently been observed that the main regulator by light in F. fujikuroi, WcoA, positively or negatively controls different SM clusters in this fungus [73]. This double positive/negative role on different pathways is frequent in these global regulatory systems, even when responding to the same signal.…”
Section: Genetic Organization and Regulation Of Sm Genesmentioning
confidence: 99%